Kinetic study of the poly(vinyl chloride)/titanium dioxide nanocomposites photodegradation under accelerated ultraviolet and visible light exposure. (31st March 2014) - Ghaebi Mehmandoust, Shadi; Alizadeh, Reza; Babaluo, Ali Akbar
<x xml:space="preserve">Abstract</x> In the present study, poly(vinyl chloride)/titanium dioxide (PVC/TiO2) nanocomposite films containing different amounts of synthesized TiO2 nanoparticles and commercial rutile powder were irradiated for 5112 hr, under exposure of artificial ultraviolet and visible lights in three different intensities. The rate of degradation was determined by using weight loss data and was found to follow a pseudo‐first order kinetic model. To determine the overall rate constant of degradation, k, a possible mechanism of the photodegradation was considered. The rate equation demonstrated k as a function of TiO2 concentration and irradiation intensity at each wavelength. The overall rate constant of PVC/TiO2 samples were calculated to be varied in the range of 6–16 × 10−7 hr−1, at all investigated conditions. The kinetic study represented that by adding synthesized TiO2 nanoparticles, even at low content, and with increasing their concentration, the photodegradation rate of nanocomposites decreased considerably compared with the composite samples. Likewise, by adding nanoparticles, a significant increase in the nanocomposites lifetime was achieved. The effect of irradiation intensity was investigated according to the reciprocity law experiments, and it was found that photodegradation occurred in two regimes with respect to irradiation intensity. The calculated overall rate constants were validated by the experimental data. Copyright © 2014 John Wiley & Sons, Ltd.